THE INFLUENCE OF SELF-CONFIDENCE AND ACTIVENESS IN STUDENT ORGANIZATIONS ON PUBLIC SPEAKING SKILLS - Samene, Veronika; Kurniawati, Rohmah (Sekolah tinggi ilmu ekonomi pemuda, 2024)
This type of research is quantitative The data collection technique in this study is multiple regression analysis. By using data collection techniques by means of questionnaires and documentation. before the questionnaire research was carried out, the validity and reliability tests were carried out using the help of the SPSS application. And with a research population of 41 students. After collecting the data, the classical assumption test was carried out. From the results of data analysis, it can be known that the coefficient of determination (R2) is 0.901 or 90.1%, meaning that this value is able to explain that the organizational culture and organizational climate variables contribute to the time discipline variable by 90.1% for the remaining 9.9% influenced by other variables outside the variables used in the study. From the results of the research that has been done, it shows that there is an influence of organizational activeness and student achievement on student work readiness, therefore it can be concluded that the more active students participate in organizations and are supported by high learning achievements, the better their work readiness will be in the world of work.